Ultrasound Doppler examination in the surgical treatment of pituitary adenomas with cavernous sinus extension - Aksyonov, Ruslan V.; Palamar, Orest I.; Huk, Andrii P.; Okonskyi, Dmytro I.; Teslenko, Dmytro S. (Ukrainian Neurosurgical Journal, 2021)
Objective: To determine the effectiveness of intraoperative Doppler ultrasound in the surgical treatment of pituitary adenomas with invasive parasellar growth into the cavernous sinus Knosp 3 and Knosp 4. Material and Methods. During 2009–2017, 71 patients with pituitary adenomas (PA) with extension into the cavernous sinus Knosp 3 and Knosp 4 were retrospectively reviewed. According to the size PA were divided into pituitary macroadenomas, (from 10 to 40 mm) in 45 (63.4%) patients, and giant PA (over 40 mm) – in 26 (36.6%) patients. Cavernous sinus invasion Knosp 3 and 4 was identified in 47 (66.2%) and 24 (33.8%) patients respectively. Non-secreting PA - 43 (60.5%) patients and hormone-secreting PA - 28 patients (39.4%). Endoscopic endonasal trassphenoidal (EET) approach was used in all cases. Laterally expanded EET (LEEET) approach was used in 29 cases. Intraoperative Doppler ultrasound (IDUS) was used in 36 (51%) cases. Results. Intraoperative Doppler ultrasound was used in cases of Knosp 3 extension in 23 (32.4%) cases and in Knosp 4 - in 13 (18.3%) cases. Gross total resection, including extension into the cavernous sinus using IDUS was achieved in 22 (62.7%) patients. In cases where IDUS was not used, gross total resection was achieved in 19 (52.7%) cases. In cases where the IDUS was not used, recurrence rate was 7.3%, with IDUS - 5%. Biochemical remission was achieved in 22 (78.6%) cases. Liquorrhea nasalis after surgery was observed in 6 (8.4%) cases, meningoencephalitis - in 1 (1.4%) case, oculomotor palsy -3 (4.2%) cases. Conclusions. Intraoperative Doppler ultrasound is an informative method that provides safe resection of pituitary adenomas with cavernous sinus extension with a low level of possible postoperative complications. Parasellar extension of Pituitary adenomas into the cavernous sinus Knosp 4 significantly reduces the possibility of gross total resection. However, the use of intraoperative ultrasound makes it possible to determine safe boundaries for manipulation both medially and laterally from the internal carotid artery, increasing the level of radicality and the duration of clinical remission. Intraoperative Doppler ultrasound during endoscopic endonasal transsphenoidal surgery of pituitary adenomas with parasellar extension allows to identify the internal carotid artery in the tumor stroma with the existing changed skull base anatomy. Dura incision under intraoperative Doppler ultrasound reduces the risk of internal carotid artery injury.